Sabasun Hyperruncit Sdn. Bhd / Abdul Hafiz Abd Latif - Abd Latif, Abdul Hafiz (2022)
Sabasun Hyperuncit Sdn Bhd is based in Malaysia with the head office in Kuala Terengganu. The enterprise operates in the supermarkets and other grocery (except convenience) stores industry. the enterprise was incorporated on december 14, 1994 for this project. I created a new look for this company starting with their logo. also, print ads supporting marketing tools tv commercials and exhibits. Of course modern concepts need to be applied to today's design, so that,it looks trendy and elegent. so, idea behind rebranding is to create a different identity for a brand from its competitors in the market.